1998
DOI: 10.1021/ac971037d
|View full text |Cite
|
Sign up to set email alerts
|

Low Blank Isotope Ratio Measurements of Rhenium, Osmium, and Platinum Using Tantalum Filaments with Negative Thermal Ionization Mass Spectrometry

Abstract: Platinum is most commonly used as a filament for Re and Os isotopic measurements, but it contains impurities of Re and Os. Tantalum is low in platinum group elements (PGE) and in Re, but it is not used for negative thermal ionization mass spectrometry because of high electron emission and high reactivity with O(2). High thermal electron emission from Ta distorts the preoptimized ion source optics. In addition, Ta consumes O(2), leaving little for samples, but O(2) is essential for isotopic ratio measurements o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 13 publications
0
8
0
Order By: Relevance
“…A highly pure Pt filament (99.99%, 1 mm × 0.025 mm, Tanaka Precious Metal Co., Japan) was used for isotope measurements, and was baked in air to a bright orange-color temperature for more than three minutes prior to loading the Re samples [19]. Some researchers have reported high Re loading blanks for Pt filaments and favored Ni, V 2 O 5 -coated Ni, or Ta filaments [19][20][21][22]. We found that the loading blank for Pt filaments used here is as low as 0.3 pg [23], which is negligible in the measurements conducted in this study.…”
Section: Reagentsmentioning
confidence: 99%
“…A highly pure Pt filament (99.99%, 1 mm × 0.025 mm, Tanaka Precious Metal Co., Japan) was used for isotope measurements, and was baked in air to a bright orange-color temperature for more than three minutes prior to loading the Re samples [19]. Some researchers have reported high Re loading blanks for Pt filaments and favored Ni, V 2 O 5 -coated Ni, or Ta filaments [19][20][21][22]. We found that the loading blank for Pt filaments used here is as low as 0.3 pg [23], which is negligible in the measurements conducted in this study.…”
Section: Reagentsmentioning
confidence: 99%
“…In this case samples will generally be analysed at higher temperatures, augmenting the chances of contamination from the spectrometer or the Pt filament. If the Re contamination is derived mainly from the filament material, it may be greatly reduced by using Ta instead of Pt filaments, which has little effect on the Re beam intensity (Frei et al 1996, Hattori et al 1998). On the other hand, if the Re blank comes mainly from the machine itself, and the use of rhenium filaments at high temperatures for the measurement of other isotopic systems is unavoidable, it may be simpler to choose another means of obtaining Re isotopic data, such as ICP-MS.…”
Section: The Negative Thermal Ionisation Mass Spectrometry Revolutionmentioning
confidence: 99%
“…Hf-W studies suggest core formation on Mars took just 5-20 Myr (Halliday et al, 2001;Kleine et al, 2004a;Dauphas and Pourmand, 2011), and core formation on Earth was largely complete by ca. 30 Myr after the start of the Solar System (Kleine et al, 2002;Yin et al, 2002;Kleine et al, 2004b). Most models consider that core formation was complete by the time of the Moon-forming impact (Hartmann and Davis, 1975;Cameron and Ward, 1976;Stevenson, 1987;Benz et al, 1987;Newsom and Sims, 1991;Canup and Asphaug, 2001;Halliday et al, 2000), and Hf-W and Sm-Nd isotopic evidence suggest that the Moon formed around 60-110 Myr after the origin of the Solar System (Touboul et al, 2007;Halliday, 2008;Halliday and Wood, 2009).…”
Section: Accretion and Differentiation Of Terrestrial Planetsmentioning
confidence: 99%
“…This Pt isotopic composition was used in IUPAC reports of elemental isotopic compositions and atomic weights until 1995, when a revised isotopic composition determined by Taylor et al (1994) using gas source mass spectrometry and electron impact ionisation of gaseous Pt(PF 3 ) 4 was adopted Taylor et al, 1994) (Table 2.1). In the late 1990s, two studies documented procedures for measurement of Pt isotopes by negative thermal ionisation mass spectrometry (N-TIMS) (Briche et al, 1997;Hattori et al, 1998). One of the groups subsequently developed a Pt isotope reference material (IRMM-010) for the Institute for Reference Materials and Measurements, for which certified values were determined using quadrupole ICPMS (Wolff (Table 2.1).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation